High Altitude Diseases: Epidemiology, Pathophysiology, Diagnosis, Prevention and Treatment - Kosek, Szymon; Klonowska, Justyna; Walkowski, Radosław; Wasiniewska , Weronika; Barański, Marcin; Kandefer, Tomasz; Sroka, Maria Izabela (Quality in Sport, 2026)
High altitude diseases—encompassing acute mountain sickness (AMS), high-altitude cerebral edema (HACE), and high-altitude pulmonary edema (HAPE)—represent a spectrum of potentially life-threatening conditions affecting individuals ascending above 2,500 meters. AMS affects 20–75% of unacclimatized travelers, while HAPE and HACE demonstrate lower incidence (0.1–15.5% and 0.5–1.5%, respectively) but substantially higher mortality without intervention. Rapid ascent exceeding 500 m/day and genetic susceptibility to hypoxic responses emerge as critical modifiable risk factors. Pathophysiological mechanisms involve hypobaric hypoxia-induced cytotoxic edema and cerebral vasodilation in AMS/HACE, mediated by hypoxia-inducible factors and blood-brain barrier disruption, while exaggerated pulmonary artery pressure elevation and capillary stress failure characterize HAPE. Diagnosis relies on clinical criteria including the Lake Louise Score for AMS, radiographic evidence for HAPE, and neurological signs with advanced imaging for HACE. Prevention strategies prioritize graded ascent (≤300 m/day above 3,000 m) and pre-acclimatization; when rapid ascent is unavoidable, acetazolamide prophylaxis (125–250 mg twice daily) reduces AMS risk by approximately 50%. Treatment algorithms emphasize immediate descent asthe gold standard, supplemented by supplemental oxygen and pharmacotherapy tailored to illness severity: acetazolamide for AMS, dexamethasone for cerebral edema, and nifedipine for pulmonary hypertension A multidisciplinary approach integrating physiological understanding with pragmatic prevention strategies, early recognition through standardized diagnostic tools, and prompt evidence-based intervention optimizes outcomes and reduces morbidity and mortality in high-altitude environments.